The macroeconomic effects of government spending shocks in New Zealand - Yifei Lyu (New Zealand Government, The Treasury, 2021)
This paper estimates the macroeconomic effects of government spending shocks in New Zealand. Using a structural vector autoregression (SVAR) model, I find small output multipliers for government consumption but large multipliers for government investment. Importantly, the real exchange rate appreciates after positive government spending shocks, consistent with classic theory. Private consumption and private investment decrease after government consumption shocks, but increase after government investment shocks. I show that selecting the appropriate series for government investment is important to estimating its effects.
Keywords: C32; E32; E62; H30; H54; 330; government consumption; government investment; New Zealand; multiplier; VAR